The reality of the use of Blackboard Learning Management System students in electronic courses at King Saud University - Al-Mulhim, Iman Abdullah; Al-Badr, Maha Ahmed; Al-Mutairin, Nora Mubarak (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the reality of using Blackboard Learning Management System in electronic courses in King Saud University. The descriptive approach based on content analysis was followed. The research group consisted of 117 students from KSU colleges, From the Faculty of Arts, the Faculty of Education, and the College of Business Administration. The tool used in this study was the questionnaire. The results of the study revealed the following:- The highest percentage of the courses studied was 23.1% and 96.6% did not receive training courses. 59.8% of the sample wanted to study other courses through the system.- Respondents' response to the extent to which the Blackboard system was used to enter intermediate e-courses ranging from (3.79 - 2.03 to 5) compared with the general average of 2.66.- The most difficult difficulties faced by students when using the system of learning management "Blackboard": lack of e-learning courses and learning management system "Blackboard" average (4.03), the difficulty of obtaining technical support at an average (4.02) and 47.4%.The researchers recommended that female students be trained in the learning management system and encouraged to use it.
Keywords: electronic courses; learning management system; blackboard; female students; King Saud University